(untitled) (Fiep Bulletin - online, 2012)
The search for scientific status is present in every field of human action and information nowadays, as aconsequence of the world development in most diverse branches of knowledge. In this frame, epistemologicaltheories have become a reference for scientific parameters in the fields of knowledge.A necessary starting point to approach epistemological theories in the field of Physical Education andSports is the postulation that Humankind has gone through conceptual evolutions ranging from the perception ofscientific rationality to scientific assumptions, epistemology and epistemological theory, itself.Among several epistemological theories, this article remarks seven of them, which the author haschosen as applicable to the field of Physical Education and Sports: The Pedagogical Theory of PhysicalEducation of Ommo Gruppe; The Psychokinetical Theory of Jean Le Boulch; The Anthropological-CulturalTheory of José Maria Cagical; The Praxeological Theory of Pierre Parlebas; The Science of Human Motricity ofManuel Sergio; The Science of Sports of Herbert Haag and the Theory of the Right to Physical/Sports Practices ofManoel Tubino.